Guest

. If a, p are the roots of the equation (x – a) (x – b) + c = 0, then the roots of the equation (x – a) (x – P) = c are (a) a, b (b) a, c (c) b, c (d) none of these

. If a, p are the roots of the equation (x – a) (x – b) + c = 0, then the roots of the equation (x – a) (x – P) = c are
(a) a, b
(b) a, c
(c) b, c
(d) none of these

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 60796 Points
one year ago
Answer: a Explaination:Reason: By given condition, (x – a) (x – b) + c = (x – α) (x – β) ⇒ (x – α) (x – β) – c = (x – a) (x – b) This shows that roots of (x – α) (x – β) – c are a and b

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free